Further triterpenes, steroids and furocoumarins from Brazilian medicinal plants of Dorstenia genus (Moraceae) - Vilegas, Janete H. Y.; Lanças, Fernando M.; Vilegas, Wagner [UNESP]; Pozetti, Gilberto L. [UNESP] (FapUNIFESP (SciELO), 1997)
The hexane-soluble fractions from the rhizomes or from the leaves from five Dorstenia (Moraceae) species (D. bahiensis Kl., D. bryoniifolia Mart ex. Miq., D. carautae C.C.Berg, D. cayapiaa Vell. and D. heringerii Car. & Val) were analysed by HRGC-MS (high-resolution gas chromatography - mass spectrometry). Pentacyclic triterpenes, steroids and furocoumarins were identified. HRGC-MS is shown to be a valuable tool for the analysis of terpenoidal compounds from Dostenia species. These compounds may be related to the folk utilization of Dorstenia species as antiophidicals.
Keywords: Dorstenia spp.(Moraceae); Furocoumarins; High resolution gas chromatography - mass spectrometry; Pentacyclic triterpenoids